Magnetotail reconnection onset caused by electron kinetics with a strong external driver - San Lu; Rongsheng Wang; Quanming Lu; V. Angelopoulos; R. Nakamura; A. V. Artemyev; P. L. Pritchett; T. Z. Liu; X.-J. Zhang; W. Baumjohann; W. Gonzalez; A. C. Rager; et al. (Nature Communications, 2020)
Magnetotail reconnection plays a crucial role in explosive energy conversion in geospace. Here, the authors show that magnetotail reconnection starts from electron reconnection in the presence of a strong external driver, which then develops into ion reconnection.